2018
DOI: 10.1101/370650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining cellular CTCF and cohesin abundances to constrain 3D genome models

Abstract: Achieving a quantitative and predictive understanding of 3D genome architecture remains a major challenge, as it requires quantitative measurements of the key proteins involved. Here we report the quantification of CTCF and cohesin, two causal regulators of topologically associating domains (TADs) in mammalian cells. Extending our previous imaging studies (Hansen et al., 2017), we estimate bounds on the density of putatively DNA loop-extruding cohesin complexes and CTCF binding site occupancy. Furthermore, co-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 74 publications
(86 reference statements)
13
56
1
Order By: Relevance
“…To test the latter possibility, we next labeled two endogenous SCC1 alleles with the same pair of orthogonal epitope tags (i.e., GFP/FLAG) at their genomic loci in the diploid yeast cells. Under the physiological protein levels, Scc1-Scc1 interaction was apparent as well ( Figure 1C, lane 4), consistent with a very recent study in mouse embryonic stem cells (mESCs) (43). Intriguingly, self-interaction was also observed for the fourth cohesin subunit, Scc3, under endogenous and overexpression conditions in diploid ( Figure 1D, lane 4) and haploid ( Figure 1E, lane 5) cells, respectively.…”
Section: Self-interactions Of Cohesin Subunits In Yeast Cellssupporting
confidence: 88%
See 2 more Smart Citations
“…To test the latter possibility, we next labeled two endogenous SCC1 alleles with the same pair of orthogonal epitope tags (i.e., GFP/FLAG) at their genomic loci in the diploid yeast cells. Under the physiological protein levels, Scc1-Scc1 interaction was apparent as well ( Figure 1C, lane 4), consistent with a very recent study in mouse embryonic stem cells (mESCs) (43). Intriguingly, self-interaction was also observed for the fourth cohesin subunit, Scc3, under endogenous and overexpression conditions in diploid ( Figure 1D, lane 4) and haploid ( Figure 1E, lane 5) cells, respectively.…”
Section: Self-interactions Of Cohesin Subunits In Yeast Cellssupporting
confidence: 88%
“…Here, we show that cohesin is dimerized in S phase and monomerized again in mitosis and G1, which is controlled by the common regulators (Eco1, Wpl1, Hos1) as the sister chromatid cohesion/dissolution cycle. Besides this biochemical evidence described here and literature (20,43), genetic interactions also support cohesin-cohesin interactions (19). Both yeast cohesin and prokaryotic SMC condensin have been proposed to act as dimers in extruding DNA loops (48,49).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recent polymer simulations 14 , however, showed that this assumption fails to explain the high degree of compaction observed in mitotic chromosomes 15 if considering asymmetric extrusion of loops by condensin, the property found in in vitro experiments 1 . Experimental evidences for both condensin 16 and cohesin [17][18][19][20] . suggested mutual interactions and a close spacing of SMC proteins 21 .…”
mentioning
confidence: 99%
“…Specifically, TAD boundaries could be brought together if the processivity, λ slow , of the slow side is larger than either the mean distance between LEFs (d) or the TAD size (L TAD ). We expect λ = λ fast + λ slow ∼ 100 − 1000 kb, d ∼ 100 − 200 kb, and L TAD ∼ 100 − 1000 kb, based on previous simulations (Fudenberg et al, 2016;, measurements of cohesin's properties, Kim et al, 2019;Golfier et al, 2020;Gerlich et al, 2006b;Kueng et al, 2006;Tedeschi et al, 2013;Hansen et al, 2017;Wutz et al, 2017;Cattoglio et al, 2019;Holzmann et al, 2019), and Hi-C maps (Dixon et al, 2012;Nora et al, 2012;Sexton et al, 2012;Rao et al, 2014). These values suggest that asymmetric two-sided loop extrusion by cohesin could generate TADs, dots, and stripes for moderate asymmetries (v slow /v fast > 0.1).…”
Section: Topologically Associated Domainsmentioning
confidence: 73%